Major differences in clinical presentation, diagnosis and management of men and women with autosomal inherited bleeding disorders. (February 2021) - Atiq, F.; Saes, J.L.; Punt, M.C.; van Galen, K.P.M.; Schutgens, R.E.G.; Meijer, K.; Cnossen, M.H.; Laros-Van Gorkom, B.A.P.; Peters, M.; Nieuwenhuizen, L.; Kruip, M.J.H.A.; de Meris, J.; et al.
Abstract: Background: In recent years, more awareness is raised about sex-specific dilemmas in inherited bleeding disorders. However, no large studies have been performed to assess differences in diagnosis, bleeding phenotype and management of men and women with bleeding disorders. Therefore, we investigated sex differences in a large cohort of well-defined patients with autosomal inherited bleeding disorders (von Willebrand disease (VWD), rare bleeding disorders (RBDs) and congenital platelet defects (CPDs)). Methods: We included patients from three nationwide cross-sectional studies on VWD, RBDs and CPDs in the Netherlands, respectively the WiN, RBiN and TiN study. In all studies a bleeding score (BS) was obtained, and patients filled in an extensive questionnaire on the management and burden of their disorder. Findings: We included 1092 patients (834 VWD; 196 RBD; 62 CPD), of whom 665 (60.9%) were women. Women were more often referred because of a bleeding diathesis than men (47.9% vs 36.6%, p = 0.002). Age of first bleeding was similar between men and women, respectively 8.9 ± 13.6 (mean ±sd) years and 10.6 ± 11.3 years ( p = 0.075). However, the diagnostic delay, which was defined as time from first bleeding to diagnosis, was longer in women (11.6 ± 16.4 years) than men (7.7 ± 16.6 years, p = 0.002). Similar results were found when patients referred for bleeding were analyzed separately. Of women aging 12 years or older, 469 (77.1%) had received treatment because of sex-specific bleeding. Interpretation: Women with autosomal inherited bleeding disorders are more often referred for bleeding, have a longer diagnostic delay, and often require treatment because of sex-specific bleeding. Funding: The WiN study was supported (in part) by research funding from the Dutch Hemophilia Foundation (Stichting Haemophilia), Shire (Takeda), and CSL Behring (unrestricted grant).